The effect of dumping syndrome severity on health-related quality of life among bariatric surgery patients in Saudi Arabia - Leena R. Baghdadi; Hoor K. Aloraini; Razan A. Almohanna; Jana I. Alhazmi; Farah M. Alhalafi; Sarah H. Alotaebe (PLoS ONE, 2026)
Dumping syndrome is a postoperative complication of bariatric surgery; it is classified into early and late dumping syndrome depending on the time of the symptoms. This study aimed to assess the health-related quality of life among adult patients in Saudi Arabia experiencing varied severity of dumping syndrome after a sleeve gastrectomy or a Roux-en-Y gastric bypass procedure. This cross-sectional study was conducted using a validated health-related quality of life questionnaire administered online to adults (≥17 years old), who had undergone bariatric surgery in Saudi Arabia. The study recruited 237 eligible adults; 142 (59.9%) of them had severe dumping syndrome. The mean physical health component summary score was 45.01 (SD = 8.42) and the mean mental health component summary score was 38.89 (SD = 9.74). Individuals with severe dumping syndrome had significantly lower (p = 0.041) physical and mental health component summary scores compared to individuals with moderate severity dumping syndrome. Higher household income was associated with higher physical and mental health summary scores. Participants who underwent gastric bypass surgery had significantly lower physical health summary scores compared to those who underwent sleeve gastrectomy. Dumping syndrome is more prevalent in women than men. The most common symptoms are a desire to lie down (79.3%) and nausea (37.9%). Patients with severe late dumping syndrome were more inclined to seek help from various healthcare providers, highlighting potential gaps in effective management strategies. These findings suggest current management approaches for severe late dumping syndrome may be insufficient, prompting the need for developing standardized treatment protocols and increasing awareness among healthcare providers. Future research should focus on evaluating the effectiveness of different therapeutic interventions and exploring strategies to improve patient outcomes and access to specialized care.